Perancangan Sistem Monitoring Kadar Kualitas Udara Menggunakan Particulate Matter 2,5 Berbasis Website - Felisia Talitha Aprilia; Ahmad Taqwa; Ade Silvia Handayani (SMATIKA JURNAL : STIKI Informatika Jurnal, 2021)
In this study, designing a mobile web to carry out the process of monitoring air quality levels that is integrated intoa system so that it is able to detect the state of air quality in the area in Palembang. This mobile web uses devices/tools at the BMKG (Meteorolog, Climatology and Geophysics Agency) Sultan Mahmud Badaruddin II Palembang that can work in real-time with an Internet of Things based platform. This research uses the SDLC (System Development Life Cycle) web development method. The results of this study are a monitoring system designed to automatically detect the state of Particulate Matter 2,5 air quality and then provide notifications to the connected gmail, without time lapse and air quality information data recording which will automatically be displayed in real-time on the user’s smartphone and give an emergency message when it is in the threshold of unhealthy or dangerous. Air quality information can be accessed online via the mobile web anywhere and anytime.